(untitled) (Journal of Atomic and Molecular Sciences, 2013)
The structural, elastic, and electronic properties of zirconium nitride (ZrN) and hafnium nitride (HfN) are investigated by first principles calculation with density functional theory. The obtained cubic NaCl structure is energetically the most stable structure at ambient pressure. A pressure induced structural phase transition from B1 to B2 phase is predicted. The estimated superconducting transition temperature (T_c) of ZrN and HfN are 9.17 K and 8.66 K respectively. As pressure increases, the superconducting transition temperature also increases.